El cacaotal mejorado: guía del facilitador - Somarriba, Eduardo; Astorga, Carlos; Cerda, Rolando; Villalobos Rodríguez, Marilyn; Say, Eduardo; Prado, Jairo; Orozco, Luis; Vásquez Morera, Nelly (2015)
CATIE (Centro Agronómico Tropical de Investigación y Enseñanza)